DAMPAK PENGGUNAAN MEDIA SOSIAL, MASALAH KESEHATAN MENTAL, DAN IKLAN TEMBAKAU TERHADAP KECEMASAN REMAJA - Saputra, Maman; Wibowo, Heribertus Rinto; Sancoko, Cahyo Harry; Goodwin, Nicholas; Basrowi, Ray Wagiu; Yuliana, Roma (Poltekkes Kemenkes Semarang, 2025)
This study examined the relationship between digital media consumption, peer influence, tobacco advertising exposure, and anxiety levels among adolescents in Jakarta, Indonesia. Using a mixed methods approach, data were collected from 1,278 junior and senior high school students through multi-stage cluster sampling surveys and focus group discussions. Quantitative results showed that 72.8% of respondents experienced anxiety, social media usage (p = 0.000), social media use at late night (OR = 2.153; 95% CI: 1.643–2.822; p = 0.000), and peer influence (OR = 2.434; 95% CI: 1.772–3.342; p = 0.000) were significantly associated with anxiety. Peer influence was identified as the strongest predictor of anxiety, nearly doubling the likelihood of experiencing anxiety. Exposure to tobacco advertising on social media showed no statistically significant association with anxiety (p = 0.162). Qualitative findings highlighted the role of peer relationships in providing emotional support and influencing smoking behaviors as coping mechanisms for anxiety. These findings emphasize the need to address social dynamics and digital media habits in adolescent mental health interventions. Policymakers and educators should prioritize strategies promoting moderated social media use and supportive peer environments to mitigate anxiety in youth within Indonesia’s evolving digital landscape.